2018
DOI: 10.1097/opx.0000000000001186
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Cognitive Demand during Sustained Near Tasks in Children and Adults

Abstract: Accommodation is more accurate and less variable when children are engaged in the task. Children also have more variable accommodation than adults. In addition, children with greater hyperopia have more variable accommodation during sustained near tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Our study is not without limitations. The first limitation of the study is that cycloplegic SE was measured on the Grand Seiko auto-refractor, whereas all experimental measures were captured using the PowerRef II 22. Most children had dilated pupil sizes of >8 mm, which is outside of the operating range of the PowerRef II and, thus, cycloplegic measures were taken using the Grand Seiko.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study is not without limitations. The first limitation of the study is that cycloplegic SE was measured on the Grand Seiko auto-refractor, whereas all experimental measures were captured using the PowerRef II 22. Most children had dilated pupil sizes of >8 mm, which is outside of the operating range of the PowerRef II and, thus, cycloplegic measures were taken using the Grand Seiko.…”
Section: Discussionmentioning
confidence: 99%
“…The PowerRef II (Plusoptix, Inc., Atlanta, GA, USA) was used to dynamically record accommodative responses during the experiments and only provides measures of refraction in the vertical meridian. Thus, the back-transformed mean RE from cycloplegic autorefraction in sphero-cylinder form was used to calculate the power in the vertical meridian (090) of the eye (described below) to combine the cycloplegic auto-refraction and power refraction measures within each subject to calculate the total accommodative response of the subject 22…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the mean accommodative response is significantly increased during active cognitive tasks [25]. Accommodative microfluctuations has also been investigated in relation to cognitive demand [26,27]. Several studies [21,28,29] have shown an increase in accommodative microfluctuations with increasing accommodative demand.…”
Section: Accommodative Microfluctuationsmentioning
confidence: 99%